Key factors influencing a decentralized IoT-based electronic government model for higher education in Iraq : an intelligent systems perspective - Fuad, Ali; Mohd Aboobaider, Burhanuddin; Abd Ghani, Mohd Khanapi (2023)
The research conducted in this study aims to identify the factors that contribute to the successful development of an e-government framework for higher education. It specifically focuses on the integration of intelligent systems. Utilizing a quantitative research approach and employing the Structural Equation Modeling (SEM) technique, specifically Partial Least Squares (PLS), the study examines the impact of various predictors, such as IT skills, technical support, technological infrastructure, rules and regulations, awareness, cultural factors, trust in government,